2016
DOI: 10.1017/cha.2016.41
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Isolated Workers in their Work with Families in Rural and Remote Australia: Exploring Peer Group Supervision

Abstract: Social workers face unique challenges in working with families, young people and children in rural and remote communities. Simultaneously, workers juggle dual relationships, personal boundaries and high visibility. Social work practise in rural Australia also faces high staff turnover, burnout and difficulties with recruitment, retention and available professional supervision. A lack of professional supervision has been identified as directly contributing to decreased worker retention in rural and remote areas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Of the articles reviewed, 36 papers were subject to full-text examination independently by two reviewers (PM and LL) to determine if they met the inclusion criteria. Subsequent to the full-text retrieval and examination process, 11 studies (nine qualitative 23,[31][32][33][34][35][36][37][38] and two quantitative 39,40 ) met the inclusion criteria. The search results, screening results and the final numbers of studies included are presented in Figure 1.…”
Section: Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the articles reviewed, 36 papers were subject to full-text examination independently by two reviewers (PM and LL) to determine if they met the inclusion criteria. Subsequent to the full-text retrieval and examination process, 11 studies (nine qualitative 23,[31][32][33][34][35][36][37][38] and two quantitative 39,40 ) met the inclusion criteria. The search results, screening results and the final numbers of studies included are presented in Figure 1.…”
Section: Search Resultsmentioning
confidence: 99%
“…Most studies included in this review reported technological issues and found them to hamper the supervision experience. 33,34,36,[38][39][40] It is essential that technological issues are proactively managed. It is also useful for the supervisee and supervisor to undertake training in the use of technology relevant to supervision.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The often vast distance from cities, and the large geographical service areas agencies are required to cover lead to rural and regional populations, including young people, being underserved in welfare provision (Darracott & Lonne, 2017;Pugh & Cheers, 2010). Closely tied to these resource inadequacies are difficulties in recruiting and retaining health and welfare professionals in non-metropolitan contexts (Nickson, Gair, & Miles, 2016). Outreach and fly-in services may be offered in some more remote areas, but 1 This definition is based on the Australian Statistical Geography Standard (ASGS) which makes distinctions between metropolitan and non-metropolitan areas.…”
Section: Introductionmentioning
confidence: 99%